2023
DOI: 10.1007/s10490-023-09879-4
|View full text |Cite
|
Sign up to set email alerts
|

Nexus of digital platforms, innovation capability, and strategic alignment to enhance innovation performance in the Asia Pacific region: a dynamic capability perspective

Abstract: The direct influence of digital platforms on organizational efficiency, financial performance, and strategy attracts the close attention of researchers. The complex mechanisms and pathways of digital platforms on transformation capacity, however, are still unclear at the global and Asia Pacific levels. Drawing on dynamic capability theory, we empirically explore how digital platforms augment organizational innovation performance. We advance the current literature on digital platforms by finding that digital pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 167 publications
0
0
0
Order By: Relevance
“…There is a need to understand the impact of DPC on performance outcomes (Cenamor et al, 2019). This impact was discussed in the literature considering a firm's competitive advantage (Mikalef & Pateli, 2017), innovation (Sedera et al, 2016;Xiao et al, 2020), innovation performance (Jiang et al, 2023;Jun et al, 2022;Khan & Tao, 2022;Sarwar et al, 2023), SMEs performance (Ramdan & Abdullah, 2021), and FP (Cenamor et al, 2019;Liu et al, 2023). For example, in their work, Cenamor et al (2019) found a positive and direct relationship between DPC and FP using a regression analysis.…”
Section: Digital Platform Capabilities and Firm Performancementioning
confidence: 99%
“…There is a need to understand the impact of DPC on performance outcomes (Cenamor et al, 2019). This impact was discussed in the literature considering a firm's competitive advantage (Mikalef & Pateli, 2017), innovation (Sedera et al, 2016;Xiao et al, 2020), innovation performance (Jiang et al, 2023;Jun et al, 2022;Khan & Tao, 2022;Sarwar et al, 2023), SMEs performance (Ramdan & Abdullah, 2021), and FP (Cenamor et al, 2019;Liu et al, 2023). For example, in their work, Cenamor et al (2019) found a positive and direct relationship between DPC and FP using a regression analysis.…”
Section: Digital Platform Capabilities and Firm Performancementioning
confidence: 99%
“…The results of the data sheet of the ideation (strategy definition) stage analysis suggest that studies in the ideation (strategy definition) stage of the business model focus on internal factors and external factors. The internal factors are mainly related to strategic decisionmaking [31,36,37], goal-driven [38,45], and organizational restructuring [33]. The external factors are associated with new market opportunities [47,50], institutional change [44], technological innovation [31,35,43], and other perspectives of the industry [34].…”
Section: Ideation (Strategy Definition) Stagementioning
confidence: 99%
“…Gaining a comprehensive understanding of BDACs and utilizing it efficiently and effectively can contribute to improving a firm's decision-making, creating value, sustaining superior innovation and firm performance, and maintaining competitiveness in dynamic environments [6][7][8]35,43,48,49].…”
Section: Big Data Analytics Capabilities (Bdacs)mentioning
confidence: 99%
“…In the era of rapid digital transformation and data-driven decision-making, strategic innovation capability (SIC) and big data analytics capabilities (BDACs) have a substantial influence over the organizational ambidexterity (OAMB) and innovation performance of organizations aspiring to thrive in the dynamic business landscape [1][2][3][4][5][6]. This study delves into the intricate relationships between these key constructs to unravel the mechanisms through which organizations can harness their SIC and BDACs to drive innovation performance (IP), with a particular emphasis on the mediating role played by OAMB.…”
Section: Introductionmentioning
confidence: 99%